Lignans from Schisandra chinensis ameliorate alcohol and CCl4-induced long-term liver injury and reduce hepatocellular degeneration via blocking ETBR. (10th August 2020) - Xu, Jin-Biao; Gao, Guang-Chun; Yuan, Ming-Jing; Huang, Xuan; Zhou, Hong-Yu; Zhang, Yang; Zheng, Ya-Xin; Wu, Zhe; Feng, Jun-Miao; Wu, Ji-Ming
Abstract: Ethnopharmacological relevance: Chemical hepatotoxicity, especially alcoholic liver injury (ALI), commonly occurs in young and middle-aged people who drink heavily. ALI is extremely harmful and can induce severe disease states, such as hepatitis, liver fibrosis, cirrhosis, or liver cancer, which are similar to CCl4 -induced liver disease states in animals. In recent studies, the pathological changes of hepatocytes and the hepatic stellate cell have shown a significant connection between endoplasmic reticulum (ER) stress and the development of liver pathology in patients. However, the detailed pathological mechanism needs to be further studied. Schisandra chinensis, (S. chinensis), a fruit-bearing vine used in Traditional Chinese Medicine (TCM), has been used to treat chronic or acute diseases, including liver disease. S. chinensis -derived lignans (SCDLs) in particular have been shown to alleviate liver pathological changes. Aim of the study: This study sought to elucidate the mechanisms underlying SCDL-mediated hepatoprotection. Materials and methods: We first used in silico target prediction and computational simulation methods to identify putative lignan-binding targets relative to the hepatoprotective effect. A gene microarray analysis was performed to identify differently expressed genes that might have significance in the disease pathological process. We then used histological analyses in a mice hepatotoxicity model to test the effectiveness of SCDLs in vivo, and a hepatocellular toxicity model to analyze the candidate-compound-mediated hepatoprotection and expression states of the key targets in vitro . Results: The in silico analysis results indicated that endothelin receptor B (ETBR/EDNRB) is likely a significant node during the liver pathological change process and a promising key target for the SCDL compound schisantherin D on the hepatoprotective effect; experimental studies showed that schisantherin D alleviated the EtOH- and ET-1-induced HL-7702 cell (belongs to liver parenchymal cell lines) injury ratio, decreased the expression of ETBR, and inhibited ECMs and ET-1 secretion in LX-2 cells (one form of hepatic stellate cells). SCDLs ameliorated EtOH- and CCl4 -induced fibrosis formation in mice liver tissue. Liver tissue western blots of SCDL-treated mice showed downregulated α-SMA, ETBR, PLCβ, CHOP, Bax, and the apoptotic factors of cleaved-caspase 12, cleaved-caspase 9, and cleaved-caspase 3 hinted at an anti-apoptosis and hepatoprotective effect. The SCDL treatment also elevated serum glutathione (GSH) and reduced the serum-transforming growth factor-β1 (TGF-β1) level. Conclusion: The findings indicated that SCDLs prevent hepatotoxicity via their anti-fibrotic, anti-oxidant, and anti-apoptosis properties. ETBR may be the key factor in promoting chemical hepatotoxicity. Graphical abstract: Image 1 Highlights: ETBR was confirmed to be a promising alcoholic liver injury treating target. In silico analysis and experimental validation was used to illustrate SCDLs mediated hepatotoxicity protection. Schisantherin D showed potential hepatotoxicity protective effect via blocking ETBR.